Rapid, B1‐insensitive, dual‐band quasi‐adiabatic saturation transfer with optimal control for complete quantification of myocardial ATP flux. Issue 6 (3rd February 2021) - Miller, Jack J.; Valkovič, Ladislav; Kerr, Matthew; Timm, Kerstin N.; Watson, William D.; Lau, Justin Y. C.; Tyler, Andrew; Rodgers, Christopher; Bottomley, Paul A.; Heather, Lisa C.; Tyler, Damian J.
Abstract : Purpose: Phosphorus saturation‐transfer experiments can quantify metabolic fluxes noninvasively. Typically, the forward flux through the creatine kinase reaction is investigated by observing the decrease in phosphocreatine (PCr) after saturation of γ ‐ATP. The quantification of total ATP utilization is currently underexplored, as it requires simultaneous saturation of inorganic phosphate ( P i ) and PCr. This is challenging, as currently available saturation pulses reduce the already‐low γ ‐ATP signal present. Methods: Using a hybrid optimal‐control and Shinnar‐Le Roux method, a quasi‐adiabatic RF pulse was designed for the dual saturation of PCr and P i to enable determination of total ATP utilization. The pulses were evaluated in Bloch equation simulations, compared with a conventional hard‐cosine DANTE saturation sequence, before being applied to perfused rat hearts at 11.7 T. Results: The quasi‐adiabatic pulse was insensitive to a >2.5‐fold variation in B 1, producing equivalent saturation with a 53% reduction in delivered pulse power and a 33‐fold reduction in spillover at the minimum effective B 1 . This enabled the complete quantification of the synthesis and degradation fluxes for ATP in 30‐45 minutes in the perfused rat heart. While the net synthesis flux (4.24 ± 0.8 mM/s, SEM) was not significantly different from degradation flux (6.88 ± 2 mM/s, P = .06) and both measures are consistent with prior work, nonlinear error analysis highlights uncertainties in the Pi ‐to‐ATP measurement that may explain a trend suggesting a possible imbalance. Conclusions: This work demonstrates a novel quasi‐adiabatic dual‐saturation RF pulse with significantly improved performance that can be used to measure ATP turnover in the heart in vivo.